Telomeric organization of a variable and inducible toxin gene family in the ancient eukaryote Giardia duodenalis. - Upcroft, P; Chen, N; Upcroft, J A

(untitled) (Genome Research, 1997)
Giardia duodenalis is the best-characterized example of the most ancient eukaryotes, which are primitively amitochondrial and anaerobic. The surface of Giardia is coated with cysteine-rich proteins. One family of these proteins, CRP136, varies among isolates and upon environmental stress. A repeat region within the CRP136 family is interchangeable by a cassette-like mechanism, generating further diversity in repeat size, copy number, and sequence. Flanking the 5' region of the CRP136 family is a novel protein kinase gene and an ankyrin homolog, creating a conserved unit. A short spacer separates the ankyrin gene from the variable, tandem array of rDNA gene units at a common breakpoint within the large subunit gene, which is followed by the (TAGGG)n telomeric sequence. Transcriptional up-regulation of the CRP136 family is accompanied by a switch in mRNA length and promoter, of de novo expression, and suggests that CRP136 mRNA induction is under the control of a telomerically regulated position effect, which evolved very early in the eukaryotic lineage.